Measuring the residence time distribution in a twin screw extruder with the use of NIR‐spectroscopy. Issue 6 (5th October 2013) - Laske, Stephan; Witschnigg, Andreas; Selvasankar, Ramesh Kumar; Holzer, Clemens
ABSTRACT The mean residence time (MRT) and the residence time distribution (RTD) of polypropylene in a twin‐screw extruder was determined directly in‐line with the help of near infrared (NIR) spectroscopy and the use of an UV‐absorber as tracer. Different experiment alignments such as screw speed, mass throughput, back pressure as well as tracer content and their influence on MRT and RTD have been investigated. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2014, 131, 39919.